Late onset esotropia in monozygous twins. Issue 3 (March 1993) - Ahmed, S; Young, J D
Abstract : Monozygous twins who developed typical acute late onset esotropia are described. Neither had evidence of other neurological disease and both responded well to bimedial rectus muscle recessions. This twin presentation suggests a hereditary basis for the development of late onset esotropia in at least some cases. It provides further support for a policy of avoiding invasive CNS investigations in those patients who have binocular potential and are otherwise normal.